The Hospital Microbiome Project: Meeting Report for the 1st Hospital Microbiome Project Workshop on sampling design and building science measurements, Chicago, USA, June 7th–8th 2012. Issue 1 (January 2013) - Smith, Daniel; Alverdy, John; An, Gary; Coleman, Maureen; Garcia-Houchins, Sylvia; Green, Jessica; Keegan, Kevin; Kelley, Scott; Kirkup, Benjamin; Kociolek, Larry; Levin, Hal; Landon, Emily; et al.
Abstract This report details the outcome of the 1st Hospital Microbiome Project workshop held on June 7th–8th, 2012 at the University of Chicago, USA. The workshop was arranged to determine the most appropriate sampling strategy and approach to building science measurement to characterize the development of a microbial community within a new hospital pavilion being built at the University of Chicago Medical Center. The workshop made several recommendations and led to the development of a full proposal to the Alfred P. Sloan Foundation as well as to the creation of the Hospital Microbiome Consortium.